Fibrinolysis vs. primary percutaneous coronary intervention for ST‐segment elevation myocardial infarction cardiogenic shock. (11th March 2021) - Vallabhajosyula, Saraschandra; Verghese, Dhiran; Bell, Malcolm R.; Murphree, Dennis H.; Cheungpasitporn, Wisit; Miller, Paul Elliott; Dunlay, Shannon M.; Prasad, Abhiram; Sandhu, Gurpreet S.; Gulati, Rajiv; Singh, Mandeep; Lerman, Amir; et al.
Abstract: Aims: There are limited contemporary data on the use of initial fibrinolysis in ST‐segment elevation myocardial infarction cardiogenic shock (STEMI‐CS). This study sought to compare the outcomes of STEMI‐CS receiving initial fibrinolysis vs. primary percutaneous coronary intervention (PPCI). Methods: Using the National (Nationwide) Inpatient Sample from 2009 to 2017, a comparative effectiveness study of adult (>18 years) STEMI‐CS admissions receiving pre‐hospital/in‐hospital fibrinolysis were compared with those receiving PPCI. Admissions with alternate indications for fibrinolysis and STEMI‐CS managed medically or with surgical revascularization (without fibrinolysis) were excluded. Outcomes of interest included in‐hospital mortality, development of non‐cardiac organ failure, complications, hospital length of stay, hospitalization costs, use of palliative care, and do‐not‐resuscitate status. Results: During 2009–2017, 5297 and 110 452 admissions received initial fibrinolysis and PPCI, respectively. Compared with those receiving PPCI, the fibrinolysis group was more often non‐White, with lower co‐morbidity, and admitted on weekends and to small rural hospitals (all P  < 0.001). In the fibrinolysis group, 95.3%, 77.4%, and 15.7% received angiography, PCI, and coronary artery bypass grafting, respectively. The fibrinolysis group had higher rates of haemorrhagic complications (13.5% vs. 9.9%; P  < 0.001). The fibrinolysis group had comparable all‐cause in‐hospital mortality [logistic regression analysis: 28.8% vs. 28.5%; propensity‐matched analysis: 30.8% vs. 30.3%; adjusted odds ratio 0.97 (95% confidence interval 0.90–1.05); P  = 0.50]. The fibrinolysis group had comparable rates of acute organ failure, hospital length of stay, rates of palliative care referrals, do‐not‐resuscitate status use, and lesser hospitalization costs. Conclusions: The use of initial fibrinolysis had comparable in‐hospital mortality than those receiving PPCI in STEMI‐CS in the contemporary era in this large national observational study.